An Unusual Orthopaedic Disease: Sarcoidosis—A Case Report - Kemah, Bahattin; Özturan, Burak; Bilgic, Bilge; Özkan, Korhan; Akpınar, Fuat; Kılıc, Bulent (The Surgery Journal, 2017)
Sarcoidosis is an idiopathic, noncaseating granulomatous disorder with wide systemic involvement. It is encountered widely around the world and it affects both sexes, all the races in all age groups. Lungs, eyes, and skin are the organs most commonly affected. Constitutional features such as weight loss, fatigue, and myalgia are the most common symptoms. Bone involvement, which is very rare, was reported as present in 3 to 13% of effected cases, and it is most commonly seen in hands and feet, compared with long bone involvement, which is extremely rare. We hereby present a case with a diagnosis of sarcoidosis and multiple bone involvement emphasizing the importance of differential diagnosis.
Keywords: sarcoidosis; bone; granulomatous disease